Analysing sources of inefficiency in the Malaysian dairy supply chain - Nurul Aisyah Mohd Suhaimi
Demand for diary products in the South-East Asia region (including Malaysia) has doubled over the past three decade. Currently, Malaysia relies heavily on imports to fulfil its domestic demand. Although milk production increased over the past decade, the growth insufficient to meet the growing domestic demand for fresh milk. This situation requires an improvement not only primary production but also at other stages in the Malaysian dairy supply chain. Therefore, analysing the sources of inefficiency in the dairy supply chain is needed in order to find out how more can be achived with less inputs required. There is no study so far that comprehensively investigated the sources of inefficiency in the Malaysian dairy supply chain. The finding of this study can provide guidance for several Malaysian stakeholders such as the Department of Veterinary Services (DVS), the Dairy Industry Development Centre (PPIT) and national and local policy makers to improve the eficiency level of the dairy sector and achieve the ambitious target of becoming self-sufficient by 10% as well as reducing dependency on imported dairy products. This thesis analysis the sources of inefficiency at the farm stage (chapter 2), at the marketing channel level (chapter 3), at the level of the main milk marketer in Malaysia, PPIT (chapter 4) and from a whole supply chain perspective (chapter 5). Chapter 1 introduces the situation in the Malaysian dairy supply chain.